Rodent consumption by hunter-gatherers in north Patagonian Andean forests (Argentina): Insights from the small vertebrate taphonomic analysis of two late Holocene archaeological sites - Andrade, Analia (2017)
Modern taphonomic studies carried out upon small rodent assemblages from arid Patagonia demonstrates rodent consumption in several late Holocene archaeological sites. Conversely, very little is known about the exploitation of these small mammals by hunter-gatherers that inhabited the North Patagonia Andean forest (NPAF). Human occupation in forests dates back to late Pleistocene – early Holocene but its use was non-existent until the late Holocene (1700 years BP), when a more recurrent and/or more extended stays in the forest took place. In order to advance in the understanding of the subsistence strategies displayed by hunter-gatherers in Patagonian forests, human involvement in the accumulation of rodent bones was evaluated from two archaeological sites located in the NPAF: Paredón Lanfré (SW Río Negro) and Risco de Azócar 1 (NW Chubut). The taphonomic analysis included the estimation of the MNE and MNI, the relative abundance, and the representation of skeletal elements. Heat alteration of bone surface and the presence of cut marks and digestion traces were also evaluated. Caviomorpha rodents dominate the small vertebrate's assemblages. Thermal alteration and differential representation of skeletal pieces –over-representation of skulls and distal elements of the limbs- suggest that human consumption was the main cause of accumulation of these rodents. The consumed species were Galea leucoblephara, Microcavia australis, Ctenomys haigi and possibly also C. sociabilis. We concluded that this consumption seems to reflect the exploitation of low ranked prey individuals in a low productive environment.